Adsorptive removal of Cu(II) by fly ash based geopolymer material. (2023) - Gupta, Nitish Kumar
Highlights: Fly ash and rice husk-based geopolymer type hybrid mass is Synthesized. This hybrid mass is a used for removal of copper from aqueous solution. Equilibrium isotherm best described by Langmuir adsorption isotherm with monolayer adsorption capacity of 28.51 mg/g. Kinetics of the reaction follows pseudo second-order kinetic model. Thermodynamic studies revealed the exothermic and spontaneous nature of the adsorption reaction. Abstract: Geopolymer are aluminosilicate inorganic polymer synthesized by polymerization of aluminosilicate with alkaline solutions. These materials possess high surface area hence promising adsorbent. In this paper fly ash and rice husk-based geopolymer type hybrid mass is applied for remediation of Cu ( II ) ions. Various adsorptive parameters for example contact /reaction time, effluent metal ions concentration, dose of hybrid mass, pH and operating temperature are optimized and fixed for getting maximum removal of aqueous Cu ( II ) ions. Equilibrium isotherm and kinetic studies revealed that the isotherm data were best described by Langmuir adsorption isotherm and the rate of adsorption follows the pseudo second-order. Thermodynamic studies carried out by applying Van't Hoff equation, which revealed that the process was exothermic and spontaneous. Results indicate encouraging performance of hybrid mass towards removal of Cu ( II ) ions.